Content and Nature of undercover investigative actions on criminal-procedural legislation of the Republic of Kazakhstan (Journal of actual problems of jurisprudence, 2018)
The article deals with the content and nature of undercover investigative actions by the new Criminal Procedure Code of the Republic of Kazakhstan. The author analyzes the specific problems associated with the results use of operational investigation in criminal proceedings, subject to the provisions specified in the Chapter 130 of the Criminal Procedure Code of the Republic of Kazakhstan.Covert surveillance (search activities) are basically operational-investigative activities which have received a new name, and an investigation officer is given the right to carry out these activities while accomplishing pretrial investigation.Key words: law, court, law, criminal cases.